2012
DOI: 10.1902/jop.2011.110044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiologic Results 12 Months After Scaling and Root Planing With Different Irrigation Solutions in Patients With Moderate Chronic Periodontitis: A Pilot Randomized Trial

Abstract: No differences were seen among the groups in the clinical results after 12 months. Regarding the microbiologic results, a slight benefit seemed to derive from the use of povidone-iodine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…These materials in high concentration, have improved the clinical results (Greenstein and Polson, Polson, 1998). However, irrigation solutions, such as chlorhexidine digluconate, povidone-iodine and sodium chloride, without SRP, have failure to demonstrate better results than SRP alone, but they were satisfactory to control periodontal disease when it is associated to SRP (Krück et al, 2011). These findings were in accordance with this study that used SRP as adjunct to lidocaine and saline solutions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These materials in high concentration, have improved the clinical results (Greenstein and Polson, Polson, 1998). However, irrigation solutions, such as chlorhexidine digluconate, povidone-iodine and sodium chloride, without SRP, have failure to demonstrate better results than SRP alone, but they were satisfactory to control periodontal disease when it is associated to SRP (Krück et al, 2011). These findings were in accordance with this study that used SRP as adjunct to lidocaine and saline solutions.…”
Section: Discussionsupporting
confidence: 86%
“…For several years, studies have been made to improve the outcomes of scaling and root planing using laser application, antibiotic systems, irrigation solutions, chlorhexidine digluconate, povidone-iodine, sodium chloride, etc (Krück et al, 2011). However, there are few reports about the effects of the local anesthetic in inflammatory process after periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Several authors have evaluated the efficacy of antiseptics as an adjunct to improving the clinical outcome and the biocide of the disease in moderate periodontitis patients, but none of them have shown a complete reduction and long term efficacy of the drug. [62223] Therefore, this randomized clinical control trial aims at evaluating the efficacy of CU as an adjunct to scaling and root planing and to compare it with the gold standard CHX solution over a period of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-gingival delivery of antimicrobial agents was shown to be potent both as in office procedures as well as home oral hygiene regime. Various anti bacterial agents such as chlorhexidine (CHX),[123] metronidazole,[4] tetracyclines,[5] and povidone-iodine[6] and herbal products such as propolis[7] and dentol,[8] have been tried in the recent past and were proven to be effective as sub-gingival irrigants in the management of shallow periodontal pockets. However, research still progresses toward identification of drugs, which are more efficient than those currently used.…”
Section: Introductionmentioning
confidence: 99%
“…Krück et al 39 reported that subgingival irrigation with 0.12% chlorhexidine did not provide any significant additional benefit in clinical and microbiologic parameters ( Aggregatibacter actinomycetemcomitans , Pg , Tf , and Td ) compared with a 0.9% sodium chloride group (control group). In the present study, subgingival irrigation with 0.2% chlorhexidine does not show any additional effect in microbiologic parameters but provides additional effects in PI, GI, and BOP.…”
Section: Discussionmentioning
confidence: 99%